DETERMINASI NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Hanan Vania Amelinda (2022)
This study aims to determine the effect of capital structure, company growth, and cash flow on firm value with profitability as moderating variable. Firm value measured by Tobin's Q. capital structure measured by debt to equity ratio. Company growth measured by net sales. Cash flow measured by cash flow from operating activity. Profitability measured by return on assets. The population in this study is the property and real estate companies listed on the Indonesian Stock Exchange for the period of 2017-2020. the sample collected in this study is 120 samples using purposive sampling method. Hypothesis testing used multiple linear regression analysis with STATA version 16. This study shows that 1) capital structure has a significant positive influence on firm value. 2) company growth has no influence on firm value. 3) cash flow has no influence on firm value. 4) profitability cannot moderate the relationship between capital structure, company growth and cash flow on firm value.